Hysteresis of two-dimensional penta-graphene thin films under uniaxial deformation - Triết, Đặng Minh; Nguyễn, Thị Bảo Trang; Trịnh, Xuân Hoàng (Hue University Journal of Science: Natural Science, 2023)
We use molecular dynamic simulations to investigate the hysteresis of two-dimensional penta-graphene under uniaxial deformation. The results show that a penta-graphene thin film with 10086 carbon atoms can withstand ultra-high strength with a maximum applied stress of ~170 GPa without failure. Under a high shear rate (0.1 Å/ps) and in the elastic regime, the penta-graphene thin film exhibits a continuous phase transformation, in which the thermodynamic parameters proportionally change with applied strain. However, at the lowest shear rate of 2 × 10–6 Å/ps, a first-order-like phase transition is observed at ~7% strain. The mean coordination number versus strain curve exhibits a sharp discontinuity of stress. Also, when reversing the shear in the linear elastic regime, the hysteresis effects become prominent at this very low strain rate. These results extend our understanding of the first-order-like structural-phase transition of two-dimensional penta-graphene thin films.